Respostas
respondido por:
10
Seja a expressão:
4x² - 2x + 18
Logo:
4 . (-3)² - 2 . (-3) + 18
4 . 9 + 6 + 18
36 + 6 + 18
60
A expressão vale 60 se x = -3.
Espero ter ajudado.
4x² - 2x + 18
Logo:
4 . (-3)² - 2 . (-3) + 18
4 . 9 + 6 + 18
36 + 6 + 18
60
A expressão vale 60 se x = -3.
Espero ter ajudado.
respondido por:
2
4 . - 2 . (-3) + 18 =
4 . 9 + 6 + 18 =
36 + 6 + 18 = 60
4 . 9 + 6 + 18 =
36 + 6 + 18 = 60
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás